(untitled) (Texas Journal of Philology, Culture and History, 2026)
The article examines the problem of forming professional speech culture in economics students, driven by modern requirements for specialists in the digital economy and globalization. The relevance of the topic lies in the fact that an economist’s successful professional activity is inextricably linked to effective communication and the ability to present analytical data persuasively. The paper defines the professional speech culture of an economist and identifies its key components: linguistic, communicative, and psychological. It analyzes the main challenges students face, such as inability to conduct business negotiations, fear of public speaking, and low business writing skills. Comprehensive methodological approaches to solving this problem are proposed and substantiated, including the integration of disciplines, the use of the case method, project activities, and specialized training. The author concludes that a systematic approach to developing speech competencies is an essential part of training highly qualified economists capable of working successfully in the modern business world